Prevalence and Antibiotic Resistance of Salmonella Sp., Shigella Sp. and Escherichia Coli in Fresh Retail Chicken in the Accra Metropolis - Guetaba, M.Y. (University of Ghana, 2015)
Prevalence and antibiotic resistance (ABR) profiles of selected food borne pathogens in retailed fresh chicken, sold in the Accra Metropolis, were investigated. Fifty (50) fresh whole chicken carcasses, purchased from commercial cold stores, open markets, meat shops and local poultry farms, in the Accra metropolis, were used. Samples for evaluation were swabs from the breast, wing and vent area of the chicken carcasses. Target pathogens, Salmonella sp., Shigella sp. and E. coli were isolated using standard microbiological and biochemical methods. Antimicrobial susceptibility was determined by the Disc diffusion method using 8 commonly used antibiotics: Ampicillin (10μg), Chloramphenicol (30μg), Cefotaxime (30ug), Ceftriaxone (30μg), Gentamicin (10μg), Cefuroxime (30ug), Cotrimoxazole (25μg) and Tetracycline (10μg). A total of 147 confirmed isolates were obtained from 3 anatomical regions: the wing, breast and the vent of the chicken dressed on the farms and those purchased from commercial cold stores. Data was analyzed using Statistical Analysis System version 12. E. coli and Salmonella sp. isolates were confirmed for both locally dressed and imported chickens. An increased likelihood of occurrence of target isolates was observed in locally dressed chicken (79.1%) compared to imported (28.9%). The number of Salmonella sp. isolates from the commercial cold stores (27.52%) was similar to that from the local farms (25.50%). Similarly the number of E. coli isolates from farms (25.50%) was not different from those isolated from markets (21.48%). No Shigella sp. isolate was confirmed. For E. coli (n=70) and Salmonella sp. (n=79) isolates respectively, resistance to Chloramphenicol was 9% to 24%; for Cefuroxime was 9.4% to 36.9%, for Cotrimoxazole; 31.5% to 40.9%; for Tetracycline; 31.5% to 47.7% and for Ampicillin; 32% to 48.3%. The Antibiotic resistance associated with Salmonella sp. was higher than for E coli. However, there was no significant difference (p>0.05) between them.
Thesis(MPHIL)-University of Ghana, 2015
Keywords: Antibiotic Resistance; Salmonella Sp., Shigella Sp.; Escherichia Coli; Fresh Retail Chicken